Are risk factors for preterm and early-term live singleton birth the same? A population-based study in France. Issue 1 (24th January 2018) - Delnord, Marie; Blondel, Béatrice; Prunet, Caroline; Zeitlin, Jennifer
Abstract : Objectives: To investigate whether risk factors for preterm (<37 weeks gestation) and early-term birth (37 and 38 weeks gestation) are similar. Design: Nationally representative cross-sectional study of births. Setting: France in 2010. Participants: Live singleton births (n=14 326). Primary and secondary outcome measures: Preterm and early-term birth rates overall and by mode of delivery (spontaneous and indicated). Risk factors were maternal sociodemographic characteristics, previous preterm birth, height, prepregnancy body mass index (BMI) and smoking, assessed using multinomial regression models with full-term births 39 weeks and over as the reference group. Results: There were 5.5% preterm and 22.5% early-term births. Common risk factors were: a previous preterm delivery (adjusted relative risk ratio (aRRR) 8.2 (95% CI 6.2 to 10.7) and aRRR 2.4 (95% CI 2.0 to 3.0), respectively), short stature, underweight (overall and in spontaneous deliveries), obesity (in indicated deliveries only), a low educational level and Sub-Saharan African origin. In contrast, primiparity was a risk factor only for preterm birth, aRRR 1.8 (95% CI 1.5 to 2.2), while higher parity was associated with greater risk of early-term birth. Conclusions: Most population-level risk factors were common to both preterm and early-term birth with the exception of primiparity, and BMI which differed by mode of onset of delivery. Our results suggest that preterm and early-term birth share similar aetiologies and thus potentially common strategies for prevention.